SUBSURFACE SURVEY OF CISARUA LAMPUNG HOT SPRINGS USING GEOCHEMICAL AND GRADIO-MAGNETIC METHOD - Reza Rizki; Wijayanti Ashuri; Rendra Aditya Hakim; Nono Agus Santoso (Engineering Faculty Universitas Lampung, 2022)
The subsurface survey was carried out in Cisarua Hot Springs, South Lampung. Cisarua Hot Springs has a neutral pH and a temperature of about 44 °C. A combination of geochemical and gradio-magnetic methods was used in this research. This research identifies the characteristics of the Cisarua Hot Springs, estimates reservoir temperature, and creates a subsurface model to determine the hot fluid distribution in the study area. According to the geological data, the manifestation of these hot springs correlates with the Lampung-Panjang Fault. The geochemical results show that this type of hot springs fluid is bicarbonate water, and the reservoir temperature is estimated to be around 160 °C. The low gradio-magnetic anomaly is correlated with the distribution of subsurface hot water flow, according to the 3D model of the gradio-magnetic method. The distribution of subsurface hot fluids is in the middle to the eastern part of the research area.